Impact Of Using Facebook On Social Relationships Of The Youth In The Kurdistan Region Of Iraq: A Field Research - Hersh R. Murad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The research focuses on identifying the most prominent impacts of using Facebook by the youth in Kurdistan region as a virtual reality in their social relationships, the extent of their harmony and interaction with the reality, and determining the positive and negative aspects of these impacts as well. Methodologically, the research is a descriptive research which depends on a survey questionnaire creating via an electronic form of the (Google Forms) application, and distributed electronically on a random sample of (848) participants. The research has founded that Facebook has not strengthen the social relationships among the youth of the region; on the contrary, it has negatively influenced these relationships.The research has also shown that the likes, comments, and sharing of friends' posts on the one hand, and the messages and chatting on the other hand did not empower these social relationships on the mentioned platform.